(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
This study investigated effect of heavy metals Zn2+, Pb2+ and Ni2+ on free proline content and superoxide dismutase activity in mosses Hylocomium splendens, Pleurozium schreberi and Rhytidiadelphus squarrosus. The effect of Cu2+ and Cr6+, low and high temperatures and osmotic stress in relation to proline content and catalase activity were estimated in hepatic Marсhantia polymorpha. It was found that proline accumulation was more pronounced under high temperatures and osmotic stress than in the presence of heavy metals. It is concluded that in tolerant species stress conditions may enhance protective processes such as accumulation of free proline and increase in the activities of detoxifying enzymes superoxide dismutase and catalase.